The Isokinetic Rugby Union Physical Work Evaluation (RUPWE) protocol: Can Rugby Union Players meet the physical work demands of the game? - Naidoo, R.; Doran, J. (South African Journal of Sports Medicine, 2021)
Background: To protect the lumbar spine from excessive forces, rugby union players need to demonstrate the work ability of the trunk extensors and flexors to meet the physical demands.